ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF ESBL PRODUCING GRAM NEGATIVE BACILLI - PRABHAKAR C MAILAPUR; DEEPA S; ABHISEK ROUTRAY (International Journal of Pharma and Bio Sciences, 2013)
The production of extended-spectrum- β lactamases (ESBLs) is an important mechanism for resistance to the cephalosporins. The proper dectection of this enzyme is important for optimal patient care. The aim of this study is to determine the prevalence and the antibiotic sensitivity pattern of ESBL producing gram negative bacilli. All the urinary isolates were collected from patient suffering from urinary tract infections were tested for ESBL production by using both the double- disk approximation and the combination disk methods. Among the 218 strains collected from clinically diagnosed UTIs patient 144(66%) were ESBL producers including E.coli – 94(43%) Klebsiella spp – 24(11%), Pseudomonos aeroginosa – 14(0.6%), Citrobacter spp – 4(0.18%), Enterobacter spp – 6(0.27%),